2021
DOI: 10.1109/twc.2020.3036444
|View full text |Cite
|
Sign up to set email alerts
|

User Pairing, Link Selection, and Power Allocation for Cooperative NOMA Hybrid VLC/RF Systems

Abstract: Despite the promising high-data rate features of visible light communications (VLC), they still suffer from unbalanced services due to blockages and channel fluctuation among users. This paper introduces and evaluates a new transmission scheme which adopts cooperative non-orthogonal multiple access (Co-NOMA) in hybrid VLC/radio-frequency (RF) systems, so as to improve both system sum-rate and fairness. Consider a network consisting of one VLC access point (AP) and multiple strong and weak users, where each wea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 47 publications
(87 reference statements)
0
41
0
Order By: Relevance
“…This new OFDM scheme design improves optimization and allocation of both power and bandwidth for both technologies which allows the network to achieve better performance. Moreover, multiple studies proposed using NOMA which appeared to be less sensitive to LOS availability compared to OFDMA [202], [255], [256]. In [255], a novel energy efficient NOMA hybrid RF/VLC system has been proposed.…”
Section: [242]mentioning
confidence: 99%
See 1 more Smart Citation
“…This new OFDM scheme design improves optimization and allocation of both power and bandwidth for both technologies which allows the network to achieve better performance. Moreover, multiple studies proposed using NOMA which appeared to be less sensitive to LOS availability compared to OFDMA [202], [255], [256]. In [255], a novel energy efficient NOMA hybrid RF/VLC system has been proposed.…”
Section: [242]mentioning
confidence: 99%
“…Authors have further demonstrated that NOMA is less sensitive to LOS compared to its OFDMA-based counterpart. In [256], multiple access techniques were performed for maximizing the overall achievable data rate where they jointly decide on the power allocation coefficients, pairing index, and link selection. However, the non-cooperative nature of NOMA makes users competing on resources.…”
Section: [242]mentioning
confidence: 99%
“…Zhu et al [12] investigated the joint power, time allocation, and user grouping to minimize the weighted sum of the energy consumption and delay in mobile edge computing systems. Obeed et al [13] proposed the jointly user pairing, link selection, and power allocation for the C-NOMA in hybrid VLC/RF systems.…”
Section: A Related Workmentioning
confidence: 99%
“…A large body of work has been produced in the application of NOMA in VLC systems, such as [13]- [16] to name a few. In [13], [14], it was shown that NOMA outperforms the traditional orthogonal frequency division multiple access (OFDMA) scheme in an indoor VLC system model serving multiple users with fixed positions and orientations.…”
Section: B Related Workmentioning
confidence: 99%
“…In [15], NOMA was investigated in a downlink multi-user VLC system with mobile and randomly oriented users, where the sum rate and outage probability were derived. In [16], a system model consisting of one AP serving multiple users simultaneously was established, where users are served using the cooperative NOMA (C-NOMA) scheme.…”
Section: B Related Workmentioning
confidence: 99%